The Effect of Internal Control and Internal Audit on the Effectiveness of Lending at PT. BRI (Persero) Tbk Unit Jatinegara Binjai - Anjani, Ramina; Junawan, Junawan (Lembaga Jurnal & Seminar Universitas Pembangunan Panca Budi, 2021)
The title of this research is “The Effect of Internal Control and Internal Audit on the Effectiveness of Credit Granting at PT. BRI (Persero) Tbk Unit Jatinegara Binjai”. This study aims to determine the effect of internal control and internal audit on the effectiveness of lending. The population used in this study were employees at PT. BRI (Persero) Tbk Unit Jatinegara Binjai. The sampling technique uses saturated samples. The sample size of 30 people. The type of data in this study are primary and secondary data. Data collection techniques using questionnaires, interviews, and documentation studies with data analysis techniques using a quantitative approach with multiple linear regression statistical tools. The results of this study indicate: 1) Internal control has a partially insignificant effect on the effectiveness of lending,